Spillage of Viable Seeds of Oilseed Rape along Transportation Routes: Ecological Risk Assessment and Perspectives on Management Efforts - Pascher, Kathrin; Hainz-Renetzeder, Christa; Gollmann, Günter; Schneeweiss, Gerald M. (Frontiers in Ecology and Evolution, 2017)
Seed spillage during handling and transportation promotes establishment and invasion of feral crops into adjacent semi-natural habitats. This is also the case for oilseed rape (OSR, Brassica napus), where seed spillage may lead to establishment of herbicide resistant OSR populations in countries without cultivation of genetically modified OSR. Using data from Austria—where cultivation and import of genetically modified OSR are banned—as a prime example, we demonstrate that ports, oil mills, switchyards, and border railway stations to countries with different electric current systems—where trains have to stop—are the sites of primary concern with respect to seed spillage. Based on the results of the Austrian case study we discuss common measures to limit crop seed spillage which include intensified controls at border railway stations and the mode of seed packing during transportation. We further recommend sufficient cleaning both of goods wagons and of loading areas of trucks and ships as well as an appropriate weed management.